Battle : a visual journey through 5,000 years of combat - Grant, R. G. (New York : DK Pub., 2009)
"Organized chronologically, Battle provides a detailed overview of the conduct of warfare through the centuries, from the first recorded battle at Megiddo between the massed ranks of Hittites and Egyptians, to the war of the missing Weapons of Mass Destruction. In each era, the technology that transformed the battlefield and the tactics that won the day are explored and explained. Battle is an indispensable reference to this most fundamental part of the human story."--Publisher description.
Warfare in the ancient world -- Between history and legend -- The might of Mesopotamia -- Greek triumphs -- Greek-Persian wars -- Greek versus Greek -- The conquests of Alexander -- After Alexander -- The conquests of the legions -- Early Rome -- The Punic wars -- Imperial Rome -- The shift to the East -- Asian empires -- Chinese warfare -- Indian warfare -- Warfare in the Middle Ages -- Invaders and feudal Lords -- Byzantium survives -- Frankish power -- Vikings and Northmen -- Warriors of Islam -- Arab advance -- Islamic impact -- The Crusades -- The First and Second Crusades -- Decline of the Crusades -- The Spanish Reconquista -- Mongol power -- Conquests in Asia and Europe -- Conquests of Timur -- East Asian warfare -- Kublai and the Ming -- Southeast Asia -- Samurai warfare -- Knights, castles, and bowmen -- Popes and emperors -- Heresy and revolt -- The Hundred Years War -- Triumph of the infantry -- Northern wars -- Rise of the Ottomans -- Early modern warfare -- Islamic empires -- Ottoman glory and decline -- Mogul India -- African empires -- Power and religion -- France's Italian wars -- Wars of religion -- The Thirty Years War -- The English Civil War -- Dynastic wars -- The great Northern war -- Warfare in the Americas -- Conquest of the Aztecs and Incas -- Conflicts in North America -- Japan, Korea, and China -- Pacifying Japan -- Korea resists Japan -- Manchu Conquest -- Empires and revolutions -- The Seven Years War -- The French and Indian War -- War in Europe and India -- The Revolutionary War -- France : revolution to empire -- French Revolutionary wars -- Napoleon takes over -- French supremacy -- The Peninsular War -- Napoleon vanquished -- Napoleon's final defeat -- Wars in the Americas -- America fights Britain -- Fighting American Indians -- War in South America -- Mexico at war -- The Civil War -- Imperial conflicts -- British India -- The conquest of Africa -- Zulu wars -- The Second Boer War -- Wars of Imperial expansion -- China, Japan, and Europe -- China in turmoil -- The rise of Japanese power -- Nationalism and modernization -- Italian unification -- Rise of the German empire -- The Crimean War and Russia in Asia -- Ottoman decline and the Balkans -- Era of world wars -- World War I -- 1914 -- The Western Front 1915 -- 1916-1917 -- Ottomans in World War I -- The Eastern Front -- 1918 -- Between the wars -- Russia and China at War -- Spanish Civil War -- Hitler's war -- Blitzkrieg -- War in the Mediterranean -- War at sea -- Invasion of the Soviet Union -- Bomber offensive -- Germany defeated in the West -- Germany defeated in the East -- The Pacific War -- Japan's high tide -- Fight back -- Conflicts since 1945 -- The Chinese Civil War -- The Korean War -- Post-Colonial wars -- The Vietnam War -- Israel's wars -- Guerrillas and terrorists -- Wars since 1980.
Includes index.
Keywords: Military history; Battles; War